ANALISIS STANDAR PELAYANAN DI BANDAR UDARA BANYUWANGI BERBASIS E-SERVICE (PERATURAN MENTERI PERHUBUNGAN NOMOR 41 TAHUN 2023) - Muhammad Zaky Ash Shidqi; Thomas Aquinas Radito (Nusantara Hasana Journal, 2025)
ABSTRACT Terminal Inspection Service (TIS) Unit is a unit of PT. Angkasa Pura Indonesia which is tasked with supervising and ensuring that airport facilities are functioning properly and ready for use. The purpose of this study was to determine the Implementation of Ministerial Regulation Number 41 of 2023 concerning Airport Service Standards carried out by Terminal Inspection Service at Banyuwangi Airport, especially in terms of facility services during the passenger departure and arrival process, services for comfort facilities, and services for value-added facilities. The airport facility supervision system carried out by TIS refers to the Minister of Transportation Regulation Number 41 of 2023 concerning Airport Services, this regulation is effective from August 7, 2023. Supervision of airport facilities is carried out periodically every day to ensure that the facilities are functioning properly and are safe to use, this is based on the principle of zero accident which is the basic principle of airport management. This study is a qualitative descriptive study using primary data obtained from filling out a daily checklist for 1 month in August 2024. Keywords: Service Standards, Ministerial Regulation Number 41 of 2023, Banyuwangi Airport